Shariah Audit, Transparency, and the Constitutional Court: Protecting Public Funds from an Islamic Economics Perspective - Ade Ananto Terminanto; Ade Sofyan Mulazid; Ridho Fikri Almi; Muhammad Iman Kurniawan; Miftah Hur Rahman Zh (Madania: Jurnal Kajian Keislaman, 2025)
This study examines the role of Shariah audit and transparency in protecting public funds from an Islamic economics perspective, with a specific focus on the Constitutional Court's role as the ultimate guardian of financial integrity. The research aims to synthesize recent literature to identify prevailing trends, analytical frameworks, and existing gaps in the field. The methodology employed is a Systematic Literature Review (SLR) following the PRISMA protocol, with a search conducted in the Scopus database yielding 50 selected articles for thematic analysis. Key results reveal that Shariah audit serves as a dual governance mechanism ensuring both financial accuracy and Shariah compliance. The Constitutional Court is conceptualized as a pivotal institution executing a modern hisbah function, wielding the authority to annul policies that enable misuse. Findings also indicate significant geographical disparities, a dominance of qualitative approaches, and the disruptive potential of technologies like blockchain and AI in enhancing transparency. However, technological implementation still faces regulatory and capacity-building challenges. The conclusion affirms the necessity of integrating ethical principles (Maqasid al Shariah), audit mechanisms, and judicial oversight. This study contributes to the literature by introducing an integrative analytical framework that links Shariah audit, technological transparency, and constitutional judicial oversight, offering a novel perspective on how modern Islamic governance can institutionalize accountability and safeguard public wealth. Penelitian ini mengkaji peran audit Syariah dan transparansi dalam melindungi dana publik dari perspektif ekonomi Islam, dengan fokus khusus pada peran Mahkamah Konstitusi sebagai penjaga utama integritas keuangan. Penelitian ini bertujuan untuk mensintesis literatur terkini guna mengidentifikasi tren yang berlaku, kerangka kerja analitis, dan kesenjangan yang ada di bidang ini. Metodologi yang digunakan adalah Systematic Literature Review (SLR) dengan mengikuti protokol PRISMA, dengan pencarian yang dilakukan dalam basis data Scopus yang menghasilkan 50 artikel terpilih untuk dianalisis secara tematik. Hasil utama mengungkapkan bahwa audit Syariah berfungsi sebagai mekanisme tata kelola ganda yang memastikan akurasi keuangan dan kepatuhan Syariah. Mahkamah Konstitusi dikonseptualisasikan sebagai institusi pivotal yang menjalankan fungsi hisbah modern, dengan kewenangan untuk membatalkan kebijakan yang memungkinkan penyalahgunaan dana. Temuan juga menunjukkan adanya disparitas geografis yang signifikan, dominan pendekatan kualitatif, dan potensi disruptif teknologi seperti blockchain dan AI dalam meningkatkan transparansi. Namun, implementasi teknologi masih menghadapi tantangan regulasi dan pengembangan kapasitas. Kesimpulan penelitian menegaskan perlunya integrasi prinsip-prinsip etika (Maqasid al-Shariah), mekanisme audit, dan pengawasan yudisial. Studi ini berkontribusi pada literatur dengan memperkenalkan kerangka analitis integratif yang menghubungkan audit Syariah, transparansi teknologi, dan pengawasan yudisial konstitusional, menawarkan perspektif baru tentang bagaimana tata kelola Islam modern dapat melembagakan akuntabilitas dan melindungi kekayaan publik.